Os Brasis alemães nos documentários de sotaque do Rio Grande do Sul: figurações das identidades sob o signo das diferenças em Walachai e Berlim Brasil - Machado, Alisson (2014)
This study aims to investigate how the documentaries Walachai (Rejane Zilles, 2009) and Berlim Brasil (Martina Dreyer e Renata Heinz, 2009) construct figurations about communities of German descent in country of the State of Rio Grande do Sul. Understanding the documentary film as a place of memory , we start from the theoretical assumption that it is possible to find certain figurations representing the perspective in which the film inscribes itself and for which builds its approach on the real. The figurations, as narrative anchors , help us to understand the processes of imagination on the other in relation to a self-enunciator (the documentarian). In this sense, using a prior literature review and the film analysis method, we seek to understand which statements and/or propositions these documentary films present about communities that received in the past the German immigrants and where their descendants live nowadays, who organize their everyday life due cultural memory inherited from their ancestors. Our attention is to understand how these documentaries, identified as examples of films belonging to an accent cinema , guided these individuals/communities and how they face the debate about cultural differences when they propose figurations of these German Brazils . Our research paradigm focuses on Buber philosophy (2003), designed by double possibility that documentarians can take to engage with the filmed subject. When documentarians assume a posture represented in the sentence I-Thou , comprise the subject in its complexity and uniqueness, allowing themselves to enter into a relationship and dialogue. In opposed, when the filmmakers take a stance I-It , demarcate an insurmountable distance to those they film, numbering and quantifying the social world on the basis of own movie goals. At the end, we believe that Walachai, marking the time and the work as signs of differences, proposes a filmic experience that aims to bring the viewers near to the universe of their social character, recognizing cultural differences as own elements of their identities. Berlim Brasil, in turn, to choose the language as a sign of differences, presents a fragmented narrative, based on the constant use of the testimony and the use of images of the social world just to prove its arguments, facing problems in taking and reveal cultural differences of their characters. Despite this difference, in terms of argumentation, both films make important efforts to recognize as legitimate the different accents that weave these German Brazils .